2012
DOI: 10.1111/j.1651-2227.2012.02725.x
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenaline use for septic shock in children: doses, routes of administration and complications

Abstract: Higher doses of noradrenaline than those suggested in the literature may be necessary to reverse hypotension and hypoperfusion. The use of noradrenaline through peripheral venous access or intra-osseous route was safe, without any adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 23 publications
3
25
1
4
Order By: Relevance
“…Indeed, our results suggest using higher dosing regimens at the initiation of norepinephrine in the most critically ill and youngest children. These findings are in keeping with observational data reported by Lampin et al [3] who highlighted the use of higher doses of norepinephrine in septic children (0.5 ± 0.4 μg kg −1 min −1 starting dose up to 2.5 ± 2.2 μg kg −1 min −1 maximum dose) than those typically recommended in the literature which suggest a starting dose at 0.3 μg kg −1 min −1 [1,2]. However, this latter starting dose may be insufficient for certain patients and thus our model could help clinicians to reach the target MAP more quickly.…”
Section: Figuresupporting
confidence: 94%
See 1 more Smart Citation
“…Indeed, our results suggest using higher dosing regimens at the initiation of norepinephrine in the most critically ill and youngest children. These findings are in keeping with observational data reported by Lampin et al [3] who highlighted the use of higher doses of norepinephrine in septic children (0.5 ± 0.4 μg kg −1 min −1 starting dose up to 2.5 ± 2.2 μg kg −1 min −1 maximum dose) than those typically recommended in the literature which suggest a starting dose at 0.3 μg kg −1 min −1 [1,2]. However, this latter starting dose may be insufficient for certain patients and thus our model could help clinicians to reach the target MAP more quickly.…”
Section: Figuresupporting
confidence: 94%
“…Norepinephrine is currently administered to patients with hypotensive distributive shock . In children, it has supplanted dopamine over the past few years as the preferred drug for sustaining and increasing systemic arterial pressure, although evidenced‐based data are poor . The amplitude of the haemodynamic response, which is primarily dependent on norepinephrine concentrations, is difficult to predict given the multitude of factors involved and clinical experience suggests broad between‐subject variability .…”
Section: Introductionmentioning
confidence: 99%
“…Norepinephrine and epinephrine are suggested for patients in dopamine-refractory shock depending on their vascular physiology at that time [6]. However, our data suggest a trend toward the use of norepinephrine as a first line vasopressor in pediatric septic shock patients in our study; this also was reported by Matt et al [14] and Lampin et al [15] The explanation of this trend is not clear but is likely due in part to a higher number of adverse events with dopamine than with norepinephrine [16]. …”
Section: Discussionsupporting
confidence: 63%
“…All vasoactive agents, including norepinephrine, may be initiated through peripheral venous (or intraosseous, if in place) access if central venous access is not readily available to avoid delays in therapy [227,228]. However, central venous access should be obtained as soon as reasonably practicable.…”
Section: Vasoactive Medicationsmentioning
confidence: 99%